Active angiogenesis in metastatic renal cell carcinoma predicts clinical benefit to sunitinib-based therapy - del Puerto-Nevado, L (Nature Publishing Group, 2014)
BACKGROUND: Sunitinib represents a widely used therapy for metastatic renal cell carcinoma patients. Even so, there is a group of patients who show toxicity without clinical benefit. In this work, we have analysed pivotal molecular targets involved in angiogenesis (vascular endothelial growth factor (VEGF)-A, VEGF receptor 2 (KDR), phosphorylated (p)KDR and microvascular density (MVD)) to test their potential value as predictive biomarkers of clinical benefit in sunitinib-treated renal cell carcinoma patients. METHODS: Vascular endothelial growth factor-A, KDR and pKDR-Y1775 expression as well as CD31, for MVD visualisation, were determined by immunohistochemistry in 48 renal cell carcinoma patients, including 23 metastatic cases treated with sunitinib. Threshold was defined for each biomarker, and univariate and multivariate analyses for progression-free survival (PFS) and overall survival (OS) were carried out. RESULTS: The HistoScore mean value obtained for VEGF-A was 121.6 (range, 10–300); for KDR 258.5 (range, 150–300); for pKDR-Y1775 10.8 (range, 0–65) and the mean value of CD31-positive structures for MVD visualisation was 49 (range, 10–126). Statistical differences for PFS (P=0.01) and OS (P=0.007) were observed for pKDR-Y1775 in sunitinib-treated patients. Importantly, pKDR-Y1775 expression remained significant after multivariate Cox analysis for PFS (P=0.01; HR: 5.35, 95% CI, 1.49–19.13) and for OS (P=0.02; HR: 5.13, 95% CI, 1.25–21.05). CONCLUSIONS: Our results suggest that the expression of phosphorylated (i.e., activated) KDR in tumour stroma might be used as predictive biomarker for the clinical outcome in renal cell carcinoma first-line sunitinib-treated patients.